The nucleolus, the kernel, and the bargaining set: An update - Elena I\~narra García; Roberto Serrano; Ken-ichi Shimomura (Brown University, Department of Economics, 2019)
One of the many important contributions in David Schmeidler's distinguished career was the introduction of the nucleolus. This paper is an update on the nucleolus and its two related supersolutions, i.e., the kernel and the bargaining set.
Keywords: C71; C72; 330; nucleolus; kernel; bargaining set